REKONSTRUKSI EKOSISTEM PENDIDIKAN INDONESIA YANG IDEAL - Feny Nida Fitriyani (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2017)
This research explains about the society conditions which have been brought by the globalization flow with many negative effects. Thus, the problem above must be solved by returning to the proper ecosystem. There are three ecosystem components which must be developed and be maximalized inÂ order to solve the society ecosystem which has been damaged. The three ecosystem components are: science, religion, and Indonesia. From those three things, so that, they will be three pillars which will build a good education ecosystem. Ecosystem will make the human do proper mimicry process accordance with the ideal mechanism. Ecosystem will make the human develop appropriate with their expectations. That is civilized society.